Biodegradable polymer fiber made from renewable raw material

JP2025041924AInactive Publication Date: 2025-03-26TREVIRA GMBH & CO KG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024230179
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-01-10
Filing Date
2024-12-26
Publication Date
2025-03-26
Estimated Expiration
Not applicable · inactive patent
Patent Text Reader

Abstract

To provide a polymer fiber made from a renewable raw material, which allows for good fiber post-processing during stretching on a conveyor line, has a biodegradable property and has a small degree of thermal shrinkage.SOLUTION: There is provided a bi-component polymer fiber, comprising: a component A (core); and a component B (shell), and the components are configured in that: (i) a melting point of a thermoplastic polymer in the component A is at least 5°C higher than a melting point of a thermoplastic polymer in the component B; (ii) a fiber material comprising the component A comprises a biopolymer A, a fiber material comprising the component B comprises a biopolymer B; and (iii) the biopolymer A is an aliphatic polyester, preferably a biopolymer containing a repeat unit of lactic acid, the biopolymer B is an aliphatic polyester, and the biopolymer B and the biopolymer A are different with respect to their chemical structure, wherein the bi-component polymer fiber has a hot air heat shrinkage measured at 110°C in a range of 0% to 10%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to biologically degradable polymeric fibers made from renewable raw materials having good physical properties, as well as their production method and use. [Background technology]

[0002] Polymer fibers, i.e. fibers based on synthetic polymers, are industrially mass-produced. For this purpose, the base synthetic polymer is processed in a melt spinning process. In this process, a thermoplastic polymer material is melted and guided in liquid form to a spinning beam by an extruder. The molten material is then guided from this spinning beam to a so-called spinning nozzle. The spinning nozzle usually has a spinning nozzle with a number of perforations from which the individual capillaries (filaments) of the fiber are drawn. In addition to the melt spinning procedure, wet or solvent spinning methods are also used to produce spun fibers. For this purpose, instead of the melt, a highly viscous solution of the synthetic polymer is drawn through a nozzle with fine perforations. Those skilled in the art refer to both methods as so-called multi-stage spinning procedures.

[0003] The polymer fibers thus produced are used in textile and / or technical applications. Here, it is advantageous for the polymer fibers to have good dispersion properties in aqueous systems, for example in the production of wetlaid fleeces. Furthermore, in textile applications, it is advantageous for the polymer fibers to have good mechanical stiffness, for example because they can function well for further processing of the fibers, for example for drawing on a conveyor line. For textile applications, it is also advantageous for the polymer fibers, especially in the form of fleeces, to have a low degree of thermal shrinkage.

[0004] For each end use or necessary intermediate processing steps, such as drawing and / or crimping, the polymeric fibers are usually modified or prepared by application of a suitable finish or layer, which is applied to the surface of the finished or to be treated polymeric fiber.

[0005] As another possibility, chemical modification can be carried out on the polymer base structure itself, for example by incorporating compounds with flame retardant effect in the main chain and / or side chains of the polymer.

[0006] Other additives such as antistatic agents or color pigments can be introduced into the molten thermoplastic polymer or polymer fibers during the multi-stage spinning process.

[0007] The dispersion behavior of polymeric fibers is influenced, inter alia, by the nature of the synthetic polymer. Thus, in particular for fibers of thermoplastic polymers, the dispersion properties in aqueous systems are influenced by the finishes or layers applied to the surface. Summary of the Invention [Problem to be solved by the invention]

[0008] In recent years, there has been a further demand for a fiber system which, in addition to being produced from renewable raw materials, not only meets the above requirements but also, wherever possible, requires no or only minor adjustments in subsequent applications, so that existing processes and machines can continue to be used.

[0009] The problem to be solved is therefore to provide polymer fibres made from renewable raw materials which have good physical properties, which allow good post-processing of the fibres, for example in drawing on a conveyor line, and which are furthermore biodegradable, yet have a low degree of thermal shrinkage. It would be even more advantageous if the composition had long-term dispersibility and could be used even after long-term storage. [Means for solving the problem]

[0010] The problem described herein is solved by a bicomponent polymer fiber according to the invention, which comprises a component A (core) and a component B (shell), wherein the melting point of the thermoplastic polymer in component A is at least 5° C. higher than the melting point of the thermoplastic polymer in component B, and wherein the fiber material comprising component A comprises a biopolymer A and the fiber material comprising component B comprises a biopolymer B.

[0011] The bicomponent polymer fibers are usually stored as tows after the spinning process and then drawn on a conveyor line and post-processed by a specific process. The tows can also be directly further processed and the introduction of the tows into so-called canisters can be partially or completely omitted.

[0012] The combination of certain biopolymers, component A (core) and component B (shell), in combination with certain orientations results in bicomponent polymer fibers according to the invention, which also have lower heat shrinkage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] polymer The polymers used according to the invention are so-called thermoplastic polycondensates based on biopolymers.

[0014] By "thermoplastic polymer" according to the present invention is meant a plastic that can be (thermoplastically) molded in a certain temperature range, preferably in the range of 25° C. to 350° C. This process is reversible, i.e. it can be optionally repeated many times by cooling and reheating to the molten state, as long as so-called thermal decomposition of the material does not occur from overheating. This is where thermoplastic polymers differ from thermosetting plastics and elastomers.

[0015] Among the so-called thermoplastic polycondensates based on biopolymers, synthetic biopolymers are preferred, in particular synthetic biopolymers suitable for melt spinning.

[0016] The term "synthetic biopolymers" in the context of the present invention refers to materials that contain biologically derived raw materials (renewable raw materials). As such, they are distinguished from traditional crude oil-based materials or plastics such as polyethylene (PE), polypropylene (PP) and polyvinyl chloride (PVC).

[0017] The bicomponent fibers are made from degradable synthetic biopolymers, where the term biologically degradable is defined, for example, as described in ASTM D5338-15 (Standard Test Method for Determining Aerobic Biodegradation of Plastic Materials Under Controlled Composting Conditions, Incorporating Thermophilic Temperatures, ASTM International, West Conshohocken, PA, 2015, www.astm.org).

[0018] Biopolymer A (core) The synthetic biopolymer A comprising component A is an aliphatic polyester, in particular a biopolymer comprising repeat units of lactic acid, hydroxybutyric acid and / or glycolic acid, preferably lactic acid and / or glycolic acid, in particular lactic acid. Polylactic acid is particularly preferred for this.

[0019] Aliphatic polyesters are understood to be those polyesters that typically have at least about 50 mol %, in some preferred embodiments at least about 60 mol %, and in more preferred embodiments at least about 70 mol % aliphatic monomers.

[0020] "Polylactic acid" is understood to mean a polymer containing lactic acid units. Such polylactic acid is usually produced by condensation of lactic acid, but also by ring-opening polymerization of lactide under suitable conditions.

[0021] According to the present invention, particularly suitable polylactic acids include poly(glycolide-co-L-lactide), poly(L-lactide), poly(L-lactide-co-ε-caprolactone), poly(L-lactide-co-glycolide), poly(L-lactide-co-D,L-lactide), poly(D,L-lactide-co-glycolide) and poly(dioxanone). Such polymers are, for example, commercially available from Boehringer Ingelheim Pharma KG (Germany) under the trade names Resomer™ GL903, Resomer™ L206S, Resomer™ L207S, Resomer™ L209S, Resomer™ L210, Resomer™ L210S, Resomer™ LC703S, Resomer™ LG824S, Resomer™ LG855S, Resomer™ LG857S, Resomer™ LR704S, Resomer™ LR706S, Resomer™ LR708, Resomer™ LR927S, Resomer™ RG509S and Resomer™ X206S.

[0022] For the purposes of the present invention, particularly preferred are polylactic acids, in particular poly-D, poly-L or poly-D,L-lactic acids.

[0023] The term "polylactic acid" generally refers to homopolymers of lactic acid, such as poly(L-lactic acid), poly(D-lactic acid), poly(DL-lactic acid), mixtures thereof, and copolymers comprising lactic acid as the major component and a small proportion, preferably less than 10 mol %, of a copolymerizable comonomer.

[0024] Other suitable materials for biopolymer A include copolymers or terpolymers based on polylactic acid, polyglycolic acid, polyalkylene carbonates (such as polyethylene carbonate), polyhydroxyalkanoates (PHAs), polyhydroxybutyrates (PHBs), polyhydroxyvalerates (PHVs), and polyhydroxybutyrate-hydroxyvalerate copolymers (PHBVs).

[0025] In the most preferred embodiment, biopolymer A is exclusively a thermoplastic polymer based on lactic acid.

[0026] The polylactic acid used according to the present invention preferably has a number average molecular weight (Mn) of at least 500 g / mol, preferably at least 1000 g / mol, most preferably at least 5000 g / mol, more preferably at least 10000 g / mol, especially at least 25000 g / mol, as measured by gel permeation chromatography or end group titration against narrow distribution polystyrene standards. Meanwhile, the number average molecular weight is preferably at most 1000000 g / mol, more preferably at most 500000 g / mol, most preferably at most 100000 g / mol, especially at most 50000 g / mol. Number average molecular weights ranging from at least 10000 g / mol to 500000 g / mol have also proven to be highly advantageous within the scope of the present invention.

[0027] The weight average molecular weight (Mw) of the preferred lactic acid polymers, particularly poly-D, poly-L or poly-D,L-lactic acid, as measured by gel permeation chromatography or end group titration against preferably narrow distribution polystyrene standards, is preferably in the range of 750 g / mol to 5,000,000 g / mol, more preferably 5,000 g / mol to 1,000,000 g / mol. The polydispersity of these polymers is preferably in the range of 1.5-5, most preferably in the range of 10000 g / mol to 500000 g / mol, in particular in the range of 30000 g / mol to 500000 g / mol.

[0028] Particularly suitable lactic acid polymers, especially poly-D, poly-L or poly-D,L-lactic acid, preferably have an intrinsic viscosity measured at 25° C. in chloroform at a polymer concentration of 0.1% in the range of 0.5 dl / g to 8.0 dl / g, preferably in the range of 0.8 dl / g to 7.0 dl / g, especially in the range of 1.5 dl / g to 3.2 dl / g.

[0029] Within the scope of the present invention, it is highly advantageous for the biopolymer, in particular the thermoplastic synthetic biopolymer, to furthermore have a glass transition temperature above 20° C., preferably above 25° C., more preferably above 30° C., most preferably above 35° C., in particular above 40° C. Within the scope of the most preferred embodiments of the present invention, the glass transition temperature of the polymer is in the range of 35° C. to 55° C., in particular in the range of 40° C. to 50° C.

[0030] Particularly suitable are also polymers having a melting temperature above 120°C, advantageously at least 130°C, preferably above 150°C and up to 250°C, more preferably up to 210°C, most preferably in the range from 120°C to 250°C, in particular in the range from 150°C to 210°C.

[0031] For this purpose, the glass temperature and melting temperature of the polymer are preferably determined by dynamic scanning calorimetry (abbreviated "DSC"). Quite particularly, the following procedure has proven advantageous in this context.

[0032] Biopolymer B (shell) The synthetic biopolymer B comprising component B is preferably a biopolymer having a melting point at least 5° C. lower than the melting point of the synthetic biopolymer A comprising component A. Preferably, the melting point of biopolymer A is at least 10° C., more preferably at least 20° C., most preferably at least 30° C., especially at least 40° C. higher than the melting point of synthetic biopolymer B.

[0033] Biopolymer B is an aliphatic polyester, in particular an aliphatic polyester having repeat units which differ from the repeat units of biopolymer A with respect to its chemical structure.

[0034] Aliphatic polyesters are understood to be those polyesters that typically have at least about 50 mol %, in some preferred embodiments at least about 60 mol %, and in more preferred embodiments at least about 70 mol % aliphatic monomers.

[0035] The biopolymer B generally has a number average molecular weight (Mn) of at least 10 000 Daltons, in particular at least 12 000 Daltons, more preferably at least 12 500 Daltons, and up to 120 000 Daltons, in particular up to 100 000 Daltons, most preferably up to 80 000 Daltons.

[0036] Number average molecular weight (Mn) is typically determined by gel permeation chromatography against narrow distribution polystyrene standards.

[0037] The biopolymer B generally has a weight average molecular weight (Mw) of at least 50,000 Daltons and up to 240,000 Daltons, in particular up to 190,000 Daltons, most preferably up to 100,000 Daltons.

[0038] Number average molecular weight (Mn) is generally determined by gel permeation chromatography against narrow distribution polystyrene standards. It is determined by the math.

[0039] Biopolymer B generally has a melt flow index, measured according to ASTM test procedure D1238-13 (ASTM D1238-13, Standard Test Method for Melt Flow Rates of Thermoplastics by Extrusion Plastometer, ASTM International, West Conshohocken, PA, 2013, www.astm.org), of 5 to 200 grams per 10 minutes, in particular 15 to 160 grams per 10 minutes, and particularly preferably 20 to 120 grams per 10 minutes. The melt flow index is the weight (in grams) of polymer that can be extruded through an opening (diameter 0.0825 inches) of an extrusion rheometer when exposed to a force of 2160 grams at 190° C. in 10 minutes.

[0040] Biopolymer B is preferably heated at a temperature of 160° C. and for 1000 s -1The apparent viscosity measured at a shear of (s = seconds) is 50 Pa·s (Pascal seconds) to 215 Pa·s, more preferably 70 Pa·s to 200 Pa·s.

[0041] It must be taken into account here that biopolymers B based on aliphatic polyesters are not only generally difficult to process if they have a high apparent viscosity, but also that with a viscosity that is apparently too low, non-stretchable fibers are generally obtained that lack tensile strength and do not have sufficient bonding capacity (thermal bonding).

[0042] Also particularly suitable is a biopolymer B having a melting temperature of above 50°C, advantageously at least 100°C, preferably above 120°C and up to 180°C, more preferably up to 160°C, most preferably in the range from 50°C to 160°C, in particular in the range from 120°C to 160°C.

[0043] The glass transition temperature of biopolymer B is preferably at least 5° C., more preferably at least 10° C., and most preferably at least 15° C. lower than the glass transition temperature of biopolymer A. The glass transition temperature is measured by DSC.

[0044] Examples of biopolymers B that may have a low melting point and a low glass transition temperature are aliphatic polyesters with a repeat unit number of at least 5 carbon atoms (e.g. polyhydroxyvalerate, polyhydroxybutyrate-hydroxyvalerate copolymers and polycaprolactone) and succinic acid-based aliphatic polymers (e.g. polybutylene succinate, polybutylene succinate adipate and polyethylene succinate). More specific examples may include polyethylene oxalate, polyethylene malonate, polyethylene succinate, polypropylene oxalate, polypropylene malonate, polypropylene succinate, polybutylene oxalate, polybutylene malonate, polybutylene succinate, as well as mixtures and copolymers of these compounds. Such aliphatic polyesters are known from the prior art (WO 2007 / 070064) and are typically synthesized by condensation polymerization of polyols with aliphatic dicarboxylic acids or anhydrides.

[0045] In the context of the present invention, polybutylene succinate and butylene succinate copolymers are particularly preferred.

[0046] In particular, biopolymer B is one that has a high melting and crystallization enthalpy and is suitable for thermal bonding. Generally, biopolymer B is selected to have a crystallinity or latent heat of fusion (ΔHf) of greater than about 25 Joules per gram ("J / g"), more preferably greater than 35 J / g, and most preferably greater than 50 J / g. The latent heat of fusion (ΔHf), latent heat of crystallization (ΔHC), and crystallization temperature are determined according to ASTM D-3418 (ASTM D3418-15, Standard Test Method for Transition Temperatures and Enthalpies of Fusion and Crystallization of Polymers by Differential Scanning Calorimetry, ASTM International, West Conshoh Measured using Differential Scanning Calorimetry ("DSC") according to the American Institute of Standards and Technology (AIST), 2015 (www.astm.org). It is determined.

[0047] The specific drawing implementation with the parameter set defined by the present invention allows the use of more affordable biopolymer B variants in addition to biopolymer B, where the bicomponent polymer fiber thus obtained has a lower thermal shrinkage. These specific drawing parameters thus allow the use of widely available biopolymer B. The specific biopolymer B used in the embodiment according to the present invention has a number average molecular weight (Mn) of at least 10000 Daltons, more preferably at least 12000 Daltons, most preferably at least 12500 Daltons, and up to 30000 Daltons, preferably up to 28000, more preferably up to 25000 Daltons.

[0048] Number average molecular weight (Mn) is typically determined by gel permeation chromatography against narrow distribution polystyrene standards.

[0049] A particular biopolymer B has a melting temperature higher than 50°C, advantageously at least 100°C, preferably higher than 120°C and up to 180°C, more preferably up to 160°C, most preferably in the range from 50°C to 160°C, in particular in the range from 120°C to 160°C.

[0050] The glass transition temperature of a particular biopolymer B is preferably at least 5° C., more preferably at least 10° C., and most preferably at least 15° C. lower than the glass transition temperature of biopolymer A. The glass transition temperature is measured by DSC.

[0051] Examples of specific biopolymers B that may have low melting points and low glass transition temperatures are aliphatic polyesters having repeating units of at least 5 carbon atoms (e.g., polyhydroxyvalerate, polyhydroxybutyrate-hydroxyvalerate copolymers, and polycaprolactone) and succinate-based aliphatic polymers (e.g., polybutylene succinate, polybutylene succinate adipate, and polyethylene succinate). More specific examples may include polyethylene oxalate, polyethylene malonate, polyethylene succinate, polypropylene oxalate, polypropylene malonate, polypropylene succinate, polybutylene oxalate, polybutylene malonate, polybutylene succinate, and mixtures and copolymers of these compounds.

[0052] In the context of the present invention, as specific biopolymers B, polybutylene succinate and butylene succinate copolymers are particularly preferred.

[0053] In particular, certain biopolymers B having high melting and crystallization enthalpies are suitable for thermal bonding. Generally, biopolymers B are selected to have a crystallinity or latent heat of fusion (ΔHf) of greater than about 25 Joules per gram ("J / g"), more preferably greater than 35 J / g, and most preferably greater than 50 J / g. The latent heat of fusion (ΔHf), latent heat of crystallization (ΔHC), and crystallization temperature are measured using differential scanning calorimetry ("DSC") according to ASTM D-3418 (ASTM D3418-15, Standard Test Method for Transition Temperatures and Enthalpies of Fusion and Crystallization of Polymers by Differential Scanning Calorimetry, ASTM International, West Conshohocken, PA, 2015, www.astm.org). will be done.

[0054] The specific biopolymer B is determined at a temperature of 190 °C (Rheo-T of Goettfert ester 1000) Melt viscosity is 200s -1 (shear) 250 Pa·s to 400 Pa·s and 1200 s -1 (shear) in the range of 125 Pa·s to 190 Pa·s, preferably 200 s -1 (shear) 260 Pa·s to 380 Pa·s and 1200 s -1 (shear ) in the range of 130 Pa·s to 180 Pa·s, more preferably 200 s -1 (shear) 275 Pa·s to 375 Pa·s and 1200 s -1 (shear) in the range of 135 Pa·s to 175 Pa·s.

[0055] Additives in Polymers A and B The above biopolymers A and B contain common additives such as antioxidants. In this regard, it has been proven that additives of the antioxidant group are unavoidable in the production and post-processing of the fibers, since the above biopolymers A and B are susceptible to oxidative degradation.

[0056] Other common additives are pigments, stabilizers, surfactants, waxes, flow promoters, solid solvents, plasticizers and other materials, such as nucleating agents, which are added to improve the processability of the thermoplastic composition.

[0057] The biopolymer B described above, and in particular the specific biopolymer B based on its described properties, already allows for a reduction in the amount of additives, in particular nucleating agents. Such nucleating agents, which are usually added, facilitate the crystallization during cooling of the fiber, which facilitates its processing. One such nucleating agent is a multicarbon acid, for example succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid and mixtures of these acids, as described in U.S. Pat. No. 6,177,193. The nucleating agent is typically present in the biopolymer B at a concentration of less than about 0.5% by weight, in some embodiments less than about 0.25% by weight, and in some embodiments less than about 0.1% by weight.

[0058] At least 90% by weight of the bicomponent fibers according to the invention comprise the aliphatic polyester biopolymers A and B described above, and typically contain less than about 10% by weight, preferably less than about 8% by weight, and more preferably less than about 5% by weight of additives in the shell-forming biopolymer B.

[0059] As mentioned above, the biopolymers described above, especially biopolymer B (shell), are susceptible to oxidative degradation and therefore require the addition of antioxidants.

[0060] Based on the combination of raw materials and post-processing selected, the amount of antioxidant can be significantly reduced, i.e., the concentration of antioxidant in biopolymer B (shell) is 0.025% to 0.2% by weight.

[0061] The bicomponent fibers according to the invention are combined into tows after spinning and post-processed on a conveyor line using methods known from the prior art, in particular they are drawn and, if necessary, further crimped or textured. The choice of specific conveyor line parameters in the drawing allows, in particular, the use of the specific biopolymers B mentioned above.

[0062] Polymer Fiber The bicomponent fibers according to the invention can be provided as finite fibers, such as so-called staple fibers, or as infinite fibers (filaments).

[0063] For better dispersibility, the fibers are preferably present as staple fibers. The length of the staple fibers is not fundamentally limited, but is generally 2 mm to 200 mm, preferably 3 mm to 120 mm, more preferably 4 mm to 60 mm.

[0064] The single yarn count of the bicomponent fibers, preferably staple fibers, according to the invention is between 0.5 dtex and 30 dtex, preferably between 0.7 dtex and 13 dtex. For some applications, counts between 0.5 dtex and 3 dtex and fiber lengths of less than 10 mm, preferably less than 8 mm, more preferably less than 6 mm, most preferably less than 5 mm are particularly well suited.

[0065] The bicomponent fibers according to the present invention exhibit low hot air heat shrinkage, each measured at 110° C., ranging from 0% to 10%, preferably from greater than 0% to 8%.

[0066] The combination of certain biopolymers, i.e. component A (core) and a certain biopolymer B as component B (shell), in combination with a certain stretching also allows the transfer of the stretching force to the core material, thereby achieving stretch-induced crystallization, which in the bicomponent polymer fibers according to the invention leads to the low thermal shrinkage as described above.

[0067] The polymer fibers according to the invention are generally produced by a conventional procedure: first, the polymer, optionally dried, is fed into an extruder; then, the molten material is spun by a conventional device having a corresponding nozzle; the exit speed at the nozzle exit face is adjusted to a spinning speed such that the fiber is produced with the desired count; the spinning speed is understood to mean the speed at which the solid filaments are drawn off.

[0068] The fibers formed can have a circular, elliptical, or any other suitable cross-section and shape.

[0069] The fiber filaments thus produced are assembled into yarns, which in turn are assembled into tows, which are first placed in canisters for further processing, and the tows intermittently stored in the canisters are picked up and made into larger spun fiber tows.

[0070] Another object of the invention is the post-treatment of the spun fiber tows produced by the disclosed method using conventional conveyor lines, generally having a density between 10 ktex and 600 ktex, with specific drawing. The feeding speed of the spun fiber tows to the drawing or drawing frame is preferably between 10 m / min and 110 m / min (feed speed). At this point, preparations can still be applied that promote drawing but do not adversely affect the following properties:

[0071] Stretching can be carried out as a one-step procedure or, optionally, in a two-step stretching process application (see, for example, U.S. Pat. No. 3,816,486 in this regard).Before and during stretching, one or more finishes can be applied in conventional manner applications.

[0072] Drawing according to the invention, especially when using a specific biopolymer B, is carried out with a draw ratio of 1.2 to 6.0, preferably 2.0 to 4.0, where the temperature during drawing of the spun tow is between 30°C and 80°C. Drawing is therefore carried out in the range of the glass transition temperature of the spun tow to be drawn. Drawing according to the invention is carried out under steam, i.e. in a so-called steam chamber, whereby the drawing point of the fibre is reached in the steam chamber. The steam chamber is usually operated at a pressure of 3 bar.

[0073] Drawing under steam in the above temperature ranges allows the thermal shrinkage of the fibers to be deliberately and controlled reduced and adjusted.

[0074] A preferred conveyor line setup is as follows: The drawing is carried out in a one-stage procedure, in the steam chamber between the draw frames S2 and S1, i.e. the drawing point of the fibre is reached in the steam chamber. All godets of S1 (usually 7) have a temperature between 30°C and 80°C. The entire drawing is carried out in the steam chamber. The steam chamber is preferably operated with a steam pressure of 3 bar.

[0075] All godets (usually 7) of the next draw frame S2 are cold, where cold and means room temperature (approximately 20°C to 35°C).

[0076] This so-called "cold drawing" mode has the advantage that the drawing is not fixed hot on the S2 under tension. The cold S2 has the advantage that there is no risk of the individual fibres sticking to the hot godet of S2.

[0077] Despite being "cold drawn", the fibers are still resistant to high temperatures with tension-free fixing in an oven and can withstand temperatures of up to 100°C without sticking.

[0078] The above-mentioned "cold drawing" is particularly suitable for polybutylene succinate (FZ71), whose melt viscosity, determined at a temperature of 190°C (Rheo-Tester 1000 from Goettfert), is: 200s -1 (shear) 250 Pa·s to 325 Pa·s and 1200 s -1 (shear) in the range of 125 Pa·s to 150 Pa·s, preferably 200 s -1 (shear) 260 Pa·s to 300 Pa·s and 1200 s -1 (shear) in the range of 130 Pa·s to 150 Pa·s, more preferably 200 s -1 (shear) 270 Pa·s to 290 Pa·s and 1200 s -1 (shear) in the range of 135 Pa·s to 145 Pa·s.

[0079] Polybutylene succinate (FZ91) is measured at a temperature of 190°C (Goettfert Rheo-Tester 1000) melt viscosity is 200s -1 (shear) 340 Pa·s to 400 Pa·s and 1200 s -1 (shear) in the range of 150 Pa·s to 190 Pa·s, preferably 200 s -1 (shear) 350 Pa·s to 390 Pa·s and 1200 s -1 (shear) in the range of 160 Pa·s to 185 Pa·s, preferably 200 s -1 (shear) 360 Pa·s to 385 Pa·s and 1200 s-1 The draw frame S2 is operated at a temperature in the range of 60°C to 100°C, i.e. all godets (usually seven) have the above temperatures, provided that the shear pressure is in the range of 165 Pa·s to 180 Pa·s.

[0080] The spun tow preferably has a density of 240 ktex to 360 ktex before drawing.

[0081] Similarly for the crimping / texturing of the drawn fibres, conventional mechanical crimping methods can be applied using commonly known crimpers, if necessary. The mechanical device for fibre crimping is preferably steam operated, e.g. a push-in chamber. However, fibres crimped using other methods, e.g. three-dimensionally crimped fibres, can also be used. To carry out the crimping, the tow is first brought to a temperature usually in the range of 50°C to 100°C, preferably 70°C to 85°C, more preferably about 78°C, and treated with a pressure of the tow infeed rollers of 1.0 bar to 6.0 bar, more preferably about 2.0 bar, a pressure in the crimping chamber of 0.5 bar to 6.0 bar, more preferably 1.5 bar to 3.0 bar, and steam of 1.0 kg / min to 2.0 kg / min, more preferably 1.5 kg / min.

[0082] In so far as the smooth or optionally crimped fibres are relaxed and / or fixed in an oven or a hot air current, this is also carried out at a temperature of at most 130°C.

[0083] To produce staple fibers, smooth or optionally crimped fibers are taken in, then chopped, optionally cured and fed as flakes to the press rolls. The staple fibers of the present invention are preferably chopped in the relaxation of a downstream mechanical chopping unit. To produce tow types, chopping can be omitted. These tow types are fed unchopped to the rolls and pressed.

[0084] Insofar as the fibers according to the present invention are shown in crimped embodiments, the degree of crimp is preferably at least 2 crimps per cm (fiber curl), preferably at least 3 crimps per cm, more preferably between 3 curls per cm and 9.8 curls per cm, most preferably between 10 ... The preferred range is between 3.9 curls per cm and 8.9 curls per cm. For applications in which textile webs are produced, values ​​of 5 to 5.5 curls per cm for the crimp are most preferred. For the production of textile webs by wet processes, the crimp may need to be adjusted in individual cases.

[0085] Textile webs can be produced from the fibers according to the invention, which is also the subject of the present invention. Due to the good dispersibility of the fibers according to the invention, such textile webs are preferably produced by the wet process.

[0086] The term "woven web" should therefore be understood in the broadest sense in the context of this specification. The woven web may be in any form produced according to web-forming techniques, which contains the fibers according to the invention. Examples of such woven webs are fleeces, in particular wet-laid fleeces, which are preferably based on staple fibers and which are produced by thermal bonding.

[0087] The fibers according to the invention also have good dispersion performance, i.e. the fibers will continue to have very good dispersion quality even after longer storage periods, for example weeks or months, in rolls or equivalent form.Furthermore, the fibers according to the invention have good long-term dispersion quality, i.e. when the fibers are dispersed in a liquid medium, for example in water, the fibers remain dispersed for a longer period and only start to settle after a longer period.

[0088] Test Method: Unless already indicated in the above description, the following measurement or test methods are used.

[0089] Count: The yarn count was determined in accordance with DIN EN ISO 1973.

[0090] Dispersibility: For the evaluation of dispersibility, the following test method was developed and applied according to the invention.

[0091] The fibers according to the invention are cut into lengths between 2 mm and 12 mm. The cut fibers are placed in a glass container (dimensions: 150 mm long, 200 mm wide, 200 mm high) filled with DI water (DI = deionized) at room temperature (25°C). The amount of fibers is 0.25 g per liter of DI water. For better evaluation, usually 1 g of fibers and 4 liters of DI water are used.

[0092] The fiber / DI water mixture is then stirred with a conventional laboratory magnetic mixer (e.g., IKAMAG RCT) and a sic magnetic fish (80 mm) for at least 3 minutes (rotation speed of about 750 rpm to 1500 rpm), after which the mixer is switched off, and it is then determined whether all the fibers have been dispersed.

[0093] This dispersion behavior of the fibers is evaluated here as follows: Not dispersed (-) Partially distributed (o) Fully Dispersed (+) The evaluation is performed based on a defined time interval.

[0094] biologically degradable The decision was based on ASTM D5338-15 (Standard Test Method for Determining Aerobic Biodegradation of Plastic Materials Under Controlled Composting Conditions, Incorporating Thermophilic Temperatures, ASTM International, West Conshohocken, P A, 2015, www.astm.org).

[0095] Number average molecular weight (Mn) Determination by gel permeation chromatography or end-group titration against narrow distribution polystyrene standards.

[0096] Weight average molecular weight (Mw) Determination by gel permeation chromatography or end-group titration against narrow distribution polystyrene standards.

[0097] intrinsic viscosity Determination by GPC at 0.1% polymer concentration in chloroform at 25°C.

[0098] Glass transition temperature and melting temperature Determination by dynamic differential scanning calorimetry (abbreviated as "DSC") according to the following procedure: DSC measurements carried out under nitrogen, calibrated against indium. Nitrogen flow was 50 ml / min; starting weight of fibers ranged from 2 mg to 3 mg.

[0099] Temperature range from -50°C to 210°C at 10K / min, followed by 5 min isothermal and finally again to -50°C at 10K / min. The final temperature is generally always about 50° C. above the highest expected melting point. DSC measurements are performed on a TA / Waters Modell Q100.

[0100] Melt Viscosity The melt viscosity was measured at 190°C using a Goettfert Rheo Tester 1000. degrees, 200s -1 (shear) and 1200s -1 (shear) is determined.

[0101] Apparent Viscosity The determination is made as explained in WO 2007 / 070064.

[0102] Melt Flow Index Determinations are made according to ASTM test method D1238-13 (ASTM D1238-13, Standard Test Method for Melt Flow Rates of Thermoplastics by Extrusion Plastometer, ASTM International, West Conshohocken, PA, 2013, www.astm.org). Melt flow index is the weight (in grams) of polymer that can be extruded through an orifice (0.0825 inch diameter) in an extrusion rheometer when exposed to 2160 grams of force at 190° C. for 10 minutes.

[0103] Latent heat of fusion The latent heat of fusion (ΔHf), latent heat of crystallization (ΔHC) and crystallization temperature are determined according to ASTM D-3418 (ASTM D3418-15, Standard Test Method for Transition Temperatures and Enthalpies of Fusion and Crystallization of Polymers by Differential Scanning Calorimetry, ASTM International, West Conshohocken, PA, 2015, www.astm.org) As measured by differential scanning calorimetry ("DSC") according to

[0104] Heat shrink From the tow sample, 12 fibers (measurement samples) are extracted. Using tweezers, they are clamped at one end in a multi-clamp and a decrimping weight is attached to the other end. The measurements are taken on bicomponent fibres of type PLA / PBS (core / shell) with a yarn count of 2.2 dtex and a crimp-free weight of 190 mg.

[0105] The multi-clamp with the attached sample is fixed to a stand, so that the sample hangs freely under a preload force on the stand. The selected starting length (usually 150 mm) is marked on each fibre. This is done by a marking line on the stand and a marking point on the sample. After marking, the attached multi-clamp is lowered and placed on a velvet sheet. There the crimp removal weight is removed and the free end of the fibre is clamped in a second multi-clamp. The sample clamped between the two multi-clamps is hung without tension on a wire rack. This wire rack is placed in the centre of a shrink oven, preheated to the correct treatment temperature (standard temperatures are 200°C, 110°C, 80°C). After a treatment time of 5 minutes the wire rack is removed from the oven. After the two multi-clamps have cooled they are removed together with the sample and placed on the velvet sheet. After an acclimatisation time of 30 minutes the back measurement can be made. For this, the measurement sample is again fitted with a crimp removal weight and hung on the stand. For the return measurement, the adjustable marking line of the stand is positioned so that the upper end of each marking point can be covered by the marking line. The length between the markings on the counter of the stand is then read off individually for each fiber with an accuracy of 1 / 10 mm.

[0106] Calculation of length change: Length change [%] = (start length [mm] - measured length [mm]) / start length [mm] x 100%

[0107] The average value of all 12 measured samples is counted.

[0108] The present invention will now be described with reference to examples, but the scope of the present invention is not limited thereto. EXAMPLES

[0109] NatureWorks raw materials PLA 6202D and BioPBS Fz71PM are bicomponent spun It was spun into the corresponding fibers by yarn technology. The concentration of PLA as the core material was 70 wt%, and the shell proportion was 30 wt%.

[0110] A spin count of 4.0 dtex was obtained with a set delivery of 331 g / min overall at an 827-hole nozzle and a withdrawal speed of 1000 m / min. Furthermore, an antioxidant was added to the PBS at an active substance concentration of 0.05% in order to reach a correspondingly good spinning behavior at a spinning temperature of 240° C. As usual, the spun material was given a finish to allow further processing.

[0111] The spun product was then processed on a conventional staple fiber line at an undrawn tow length of about 42 ktex.

[0112] The following textile-technically significant values ​​of the variant stretched in steam medium at 2.2 dtex, set at 90° C. in an air circulating oven and crimped were obtained for further processing in an air procedure: Linear density: 2.3dtex Hardness: 28cN / tec Stretching: 41% Shrinkage (110℃): 1.5% Crimp: 5Bg / cm

[0113] BioPBS Fz71PM is a 200s -1 (shear) at 279 Pa·s and 1200 s -1 It is a polybutylene succinate with a melt viscosity (190°C) of 139 Pa·s at shear.

[0114] PLA6202D is 1.24g / cm 3 (according to ASTM D792) and a melt flow index (g / 10 min at 210°C) in the range of 15 to 30. The glass transition temperature is 55°C to 60°C (according to ASTM D3417), and the crystalline melting temperature is 160°C to 170°C (according to ASTM D3418).

Claims

1. A bicomponent polymer fiber, said fiber comprising component A (core) and component B (shell); (i) the melting point of the thermoplastic polymer in component A is at least 5° C. higher than the melting point of the thermoplastic polymer in component B; (ii) the textile material comprising component A comprises biopolymer A and the textile material comprising component B comprises biopolymer B; (iii) the biopolymer A is an aliphatic polyester, preferably a biopolymer comprising repeating units of lactic acid, and the biopolymer B is an aliphatic polyester, and the biopolymer B and the biopolymer A differ with respect to their chemical structure; In bicomponent polymer fibers, The bicomponent polymer fiber is characterized in that the hot air heat shrinkage rate measured at 110°C is in the range of 0% to 10%.

2. 2. The polymer fiber of claim 1, wherein said biopolymer A and said biopolymer B are each a biologically degradable synthetic biopolymer according to ASTM D5338-15.

3. 3. The polymer fibre according to claim 1 or 2, characterized in that the biopolymer A comprises repeating units of lactic acid, repeating units of hydroxybutyric acid and / or repeating units of glycolic acid, preferably repeating units of lactic acid and / or repeating units of glycolic acid, in particular repeating units of lactic acid.

4. 4. The polymer fibre according to claim 1 , 2 or 3, characterized in that the biopolymer A is a polylactic acid having a number average molecular weight (Mn) of at least 500 g / mol, preferably at least 1000 g / mol, more preferably at least 5000 g / mol, most preferably at least 10000 g / mol and in particular at least 25000 g / mol.

5. 5. The polymer fibre according to claim 1 , wherein the biopolymer A is a polylactic acid having a number average molecular weight (Mn) of at most 1 000 000 g / mol, preferably at most 500 000 g / mol, in particular at most 100 000 g / mol.

6. 4. The polymer fibre according to claim 1, 2 or 3, characterized in that the biopolymer A is a polylactic acid having a weight average molecular weight (Mw) in the range of 750 g / mol to 5,000,000 g / mol, preferably in the range of 5,000 g / mol to 1,000,000 g / mol, more preferably in the range of 10,000 g / mol to 500,000 g / mol and most preferably in the range of 30,000 g / mol to 500,000 g / mol, and the polydispersity of these polymers is in the range of 1.5 to 5.

7. 7. Polymer fibres according to one or more of the preceding claims, characterised in that the biopolymer A is a polylactic acid having an intrinsic viscosity, measured at 25°C in chloroform at a concentration of 0.1% polymer, in the range of 0.5 dl / g to 8.0 dl / g, preferably in the range of 0.8 dl / g to 7.0 dl / g, more preferably in the range of 1.5 dl / g to 3.2 dl / g.

8. 8. The polymer fibre according to one or more of the preceding claims, characterized in that the biopolymer A has a glass transition temperature higher than 20°C, preferably higher than 25°C, in particular higher than 30°C, more preferably higher than 35°C, in particular higher than 40°C.

9. The biopolymer B has a molecular weight of at least 10,000 Daltons, in particular at least 12,000 Daltons.

9. The polymer fibre according to claim 1, characterized in that it has a number average molecular weight (Mn) of at least 12,500 Daltons, more preferably at most 120,000 Daltons, in particular at most 100,000 Daltons, most preferably at most 80,000 Daltons.

10. 9. The polymer fibre according to claim 1 , wherein the biopolymer B has a weight average molecular weight (Mw) of at least 50,000 Daltons and up to 240,000 Daltons, in particular up to 190,000 Daltons, most preferably up to 100,000 Daltons.

11. 11. The polymer fibre according to one or more of the preceding claims, characterized in that the biopolymer B has a melt flow index, measured according to ASTM test method D1238-13, of between 5 and 200 grams per 10 minutes, in particular between 15 and 160 grams per 10 minutes, more preferably between 20 and 120 grams per 10 minutes.

12. 12. The polymer fibre according to one or more of the preceding claims, characterized in that said biopolymer B has a glass transition temperature that is at least 5°C lower, more preferably at least 10°C lower, most preferably at least 15°C lower than the glass transition temperature of said biopolymer A.

13. 13. Polymer fibres according to one or more of claims 1 to 12, characterised in that the biopolymer B is an aliphatic polyester having a repeat unit number of at least 5 carbon atoms, preferred biopolymers B being polyhydroxyvalerate, polyhydroxybutyrate-hydroxyvalerate copolymers and aliphatic polymers based on polycaprolactone and succinate, in particular polybutylene succinate, polybutylene succinate adipate and polyethylene succinate, as well as polyethylene oxalate, polyethylene malonate, polyethylene succinate, polypropylene oxalate, polypropylene malonate, polypropylene succinate, polybutylene oxalate, polybutylene malonate, polybutylene succinate and mixtures and copolymers of these compounds.

14. 14. The polymer fibre according to claim 13, characterized in that the biopolymer B is a polybutylene succinate and / or a polybutylene succinate copolymer.

15. 15. The polymer fibre according to one or more of the preceding claims, characterized in that the polymer fibre is drawn after spinning in the form of a tow, the temperature during the drawing of the tow being between 30°C and 80°C, thus above the glass transition temperatures of the biopolymers A and B, and the drawing being carried out in exposure to steam, preferably at a draw ratio of between 1.2 and 6.

0.

16. 16. The polymer fiber of claim 15, wherein the spun tow has a count of 240 ktex to 360 ktex before drawing.

17. 17. The polymer fibre according to claim 15 or 16, characterized in that the biopolymer B has a number average molecular weight (Mn) of at least 10 000 Daltons, in particular at least 12 000 Daltons, more preferably at least 12 500 Daltons and up to 30 000 Daltons, in particular up to 28 000 Daltons, most preferably up to 25 000 Daltons.

18. The biopolymer B was mixed for 200 s. -1 (shear) 250 Pa·s to 400 Pa·s and 1200 s -1 (shear) in the range of 125 Pa·s to 190 Pa·s, preferably 200 s -1 (shear) 260 Pa·s to 380 Pa·s and 1200 s -1 (shear) in the range of 130 Pa·s to 180 Pa·s, more preferably 200 s -1 (shear) 275P a·s to 375 Pa·s and 1200 s -1 18. The polymer fiber according to claim 17, characterized in that it has a melt viscosity, determined at a temperature of 190°C, in the range of 135 Pa·s to 175 Pa·s (shear).

19. A textile web comprising polymeric fibers according to claims 1 to 18, in particular obtained from a wet-laid procedure.

20. Use of polymer fibers according to claims 1 to 18 for the preparation of an aqueous suspension.